Implementasi Data Mining Menggunakan Algoritma Apriori Untuk Menentukan Tata Letak Obat - Pratiwi, Widya; Fitriana, Ayu; Sinawati, Sinawati; Zulhilmi, Hafizhan (Journal of Big Data Analytic and Artificial Intelligence, 2025)
The role of information systems has expanded to other layers of life, especially business sectors operating in the health sector. Improving service and performance productivity in the health sector, one of which is pharmacies. This study aims to identify drug dispensing patterns at 24-hour pharmacies in Tarakan. A 24 hour ready pharmacy is a business place that operates in the field of selling medicines, the sales are still manual and the data is stored as an archive, so there is no application that can help the pharmacy owner in knowing the combination of medicines purchased and in determining the layout of medicines that are still not in accordance with the requirements. alphabetical order, based on tablet drug category. This research aims to determine the relationship between drugs purchased by consumers and how to implement data mining to determine the combination of drug sales at 24 Hour Ready Pharmacies. This research was carried out in several stages. The first stage creates tabular transaction data. The second stage is to determine minimum support and minimum confidence. The third stage is to calculate itemset combinations. The fourth stage is calculating confidence and the fifth stage is making a rule or decision rule..